2007
DOI: 10.1631/jzus.2007.b0560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of perioperative autologous versus allogeneic blood transfusion on the immune system in gastric cancer patients

Abstract: Abstract:Background: Allogeneic blood transfusion-induced immunomodulation (TRIM) and its adverse effect on the prognosis of patients treated surgically for cancer remain complex and controversial. However, the potential risk associated with allogeneic blood transfusion has heightened interest in the use of autologous blood transfusion. In the present study, the serum concentrations of neopterin, interferon-gamma (IFN-γ), T lymphocyte subsets (CD3 + ratio had significantly decreased after operation, but decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 27 publications
2
33
1
1
Order By: Relevance
“…27,28 Interestingly, autologous transfusions have induced lesser degrees of immunosuppression than allogeneic transfusions in patients with gastric cancer. 29 However, several studies have theorized that there may be an undiscovered viral or molecular vector that can potentially transmit through a blood transfusion. 7,9,15,18 Data from the Surveillance, Epidemiology, and End Results program showed that in the 1970s and 1980s the overall ageadjusted incidence of NHL had increased by 3% to 4% yearly.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Interestingly, autologous transfusions have induced lesser degrees of immunosuppression than allogeneic transfusions in patients with gastric cancer. 29 However, several studies have theorized that there may be an undiscovered viral or molecular vector that can potentially transmit through a blood transfusion. 7,9,15,18 Data from the Surveillance, Epidemiology, and End Results program showed that in the 1970s and 1980s the overall ageadjusted incidence of NHL had increased by 3% to 4% yearly.…”
Section: Discussionmentioning
confidence: 99%
“…However, reinfusion of unwashed anticoagulated salvaged blood caused NKp cells to rise above preoperative levels, accompanied by enhanced interferon (IFN)-γ synthesis and macrophage activation, suggesting that PTI had been reversed [20,23]. This was supported by studies from others showing enhanced post-operative immunity following reinfusion of fresh anti-coagulated autologous blood [24,25].…”
Section: Introductionmentioning
confidence: 98%
“…In the tumor microenvironment, there is a delicate balance between antitumor immunity and tumor-originated proinfl ammatory activity, which weakens antitumor immunity [12][13][14]. Many researchers have reported that perioperative blood transfusion [15,16], postoperative Abstract Increasing evidence is being reported regarding the hypothesis that several proinfl ammatory and anti-infl ammatory cytokines may promote tumor progression and affect the host antitumor response. However, the manner in which a local cytokine network operates in tumor development remains unclear.…”
mentioning
confidence: 99%